Geographic Embeddedness of Higher Education Institutions in the Migration Policy Domain - Bozheva, Alexandra (Journal of International Students, 2020)
In 2014, Canada issued its first International Education Strategy, articulating targets for international enrollment and its economic benefits, but lacking international student retention goals. Universities and colleges used to be places where students could get immigration advice, but past Bill C-35 only Regulated Canadian Immigration Consultants can provide such advice. There is no requirement for institutions to hire these consultants. I investigate the geographic stretch of the education domain’s engagement with retention, through an examination of immigration advising support provision across Canada’s campuses. This provision is highly uneven, with a moderate association with school size, reflecting the voluntary nature of such engagement. A defined international student retention strategy could possibly change the current state of immigration governance through the education domain.